The Role of Digital Marketing in Modern Business - Islomova , Mohlaroyim (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
In this article, we will discuss how digital marketing has become an integral part of business today.Through the Internet, social networks and mobile platforms, companies have the opportunity to communicate directly with customers, promote their brand and increase sales. This article discusses the main tools of digital marketing, their importance in modern business, effective strategies and future prospects. The article also analyzes the role of digital marketing in optimizing business processes, strengthening customer relationships and increasing brand loyalty.